Blended Islamic Finance sebagai Strategi Pembiayaan Pembangunan Berbasis Keadilan Sosial - Atina Salsabila; Fauzan Fauzan; M.F. Hidayatullah (MENAWAN : Jurnal Riset dan Publikasi Ilmu Ekonomi, 2026)
The growing demand for development financing requires funding models that are not only economically effective but also capable of promoting social justice. In this context, blended Islamic finance has emerged as an approach that integrates Islamic social finance instruments with commercial financial instruments to support inclusive and sustainable development. This study aims to examine the concept of blended Islamic finance, analyse the integration patterns of sukuk, zakat, waqf, and Islamic microfinance in contemporary academic literature, and develop a conceptual simulation of a regional development financing model based on Sharia principles. The study employs a Systematic Literature Review (SLR) method through a critical synthesis of relevant scholarly publications on blended Islamic finance and development financing. The findings indicate that the integration of Islamic social and commercial financial instruments consistently generates greater impacts on social welfare improvement, economic inequality reduction, and financial inclusion expansion than the use of single instruments. Furthermore, risk-sharing and equity-based financing models are found to be the principal foundations for enhancing efficiency, sustainability, and equitable distribution of benefits. The conceptual simulation of the regional development financing model demonstrates that development funding requirements can be met through the optimisation of domestic resources derived from zakat, waqf, sukuk, and Islamic microfinance, which have not yet been fully utilised. This study concludes that blended Islamic finance possesses significant potential as a sustainable and inclusive development financing architecture that is aligned with the objectives of social justice in Islamic economics.